2016
DOI: 10.1097/01.sa.0000490909.07423.1b
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Mortality Prediction Model for Patients Receiving 14 Days of Mechanical Ventilation

Abstract: Objectives-The existing risk prediction model for patients requiring prolonged mechanical ventilation is not applicable until after 21 days of mechanical ventilation. We sought to develop and validate a mortality prediction model for patients earlier in the ICU course using data from day 14 of mechanical ventilation.Study Design-Multi-center retrospective cohort study.Patients-Adult patients receiving at least 14 days of mechanical ventilation at 5 medical centers (development cohort) or enrolled in the ARDS N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Consequently, we could not use the prognostic model proposed by Carson et al 23 to predict our subjects' 1-y mortality. 11 However, a comparison of subject characteristics is shown in table 1. Also, despite the small sample size and the design of our study, the risk factors for weaning that it revealed are consistent with current evidence; a follow-up study with a larger sample size is needed to verify our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, we could not use the prognostic model proposed by Carson et al 23 to predict our subjects' 1-y mortality. 11 However, a comparison of subject characteristics is shown in table 1. Also, despite the small sample size and the design of our study, the risk factors for weaning that it revealed are consistent with current evidence; a follow-up study with a larger sample size is needed to verify our findings.…”
Section: Discussionmentioning
confidence: 99%
“…4 In 2005, Medicare-eligible patients who required PMV ranked third in summative in-patient charges by diagnostic groups and first in charges per patient. 9 Despite receiving such a high level of care, 29 -49% of PMV patients died in the hospital, 10,11 only 19% could be discharged home, 10 and Ͻ50% of PMV hospital survivors survived more than 1 y. 3,[10][11][12][13][14] Compared with withdrawal of ventilation, providing PMV to the basecase patient costs $55,460 per life-year gained and $82,411 per quality-adjusted life-year gained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose these scoring systems since they are established systems in the literature, are fairly easy to calculate and the data needed to calculate the scores is available in the medical record. The more recently described ProVent version 14 has only recently been validated outside of the cohort in which it was developed (patients who require prolonged mechanical ventilation), 17,19 so it was not considered in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] However, there have been no reports of the use of these scoring systems in the subset of critically ill patients undergoing tracheotomy. 17 We undertook the following study to determine whether LODS and/or SOFA scores would be useful in the subpopulation of critically ill patients who undergo tracheotomy, to predict survival and other tracheotomy-specific outcomes. Our perception was that this subpopulation of patients for whom tracheotomy is requested had a worse outcome than the general population of critically ill patients.…”
Section: Introductionmentioning
confidence: 99%